2016
DOI: 10.3201/eid2212.160450
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Live Poultry Market Interventions on Influenza A(H7N9) Virus, Guangdong, China

Abstract: Temporary closure of these markets appears not to have halted virus transmission or prevented its dissemination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 25 publications
2
26
0
Order By: Relevance
“…Chilled chickens are slaughtered and packaged chicken stored at between 0°C and 4°C after going through a chilling process and has a shelf-life of 5-7 days, which can highly reduce the risk of virus transmission from live poultry to human [23]. Since the outbreaks of H7N9, many cities that reported the cases have launched a pilot program (named "Centralized Slaughtering, Cold Chain Delivery, Chilled Poultry Supply") in designated areas, such as 2013 in Shanghai, 2014 in Guangzhou and Shenzhen [11].…”
Section: Lpms Reopen and Temporary Interventions Cannot Completely Hamentioning
confidence: 99%
See 1 more Smart Citation
“…Chilled chickens are slaughtered and packaged chicken stored at between 0°C and 4°C after going through a chilling process and has a shelf-life of 5-7 days, which can highly reduce the risk of virus transmission from live poultry to human [23]. Since the outbreaks of H7N9, many cities that reported the cases have launched a pilot program (named "Centralized Slaughtering, Cold Chain Delivery, Chilled Poultry Supply") in designated areas, such as 2013 in Shanghai, 2014 in Guangzhou and Shenzhen [11].…”
Section: Lpms Reopen and Temporary Interventions Cannot Completely Hamentioning
confidence: 99%
“…To prevent the poultry-to-human transmission of this novel virus, many cities in the pearl and Yangtze river deltas implemented the LPMs closure. Once the confirmed H7N9 cases were reported in a city, the government implemented the LPMs closure and slaughtered or transferred the live poultries to decrease the disease-causing contact chance, and the numbers of new-onset human H7N9 viral infections decreased rapidly [10,11] [12]. For instance, one strict prevention and control measures were used to conduct in Guangdong Province, which was daily cleaning of the market, weekly disinfection of the market and monthly closings of the live market.…”
Section: Introductionmentioning
confidence: 99%
“…The physical location of the LBM is only one among many possible transaction sites. Our results showed that temporary market closure for 7 days is likely to lead to establishment of parallel, informal, and uncontrolled live poultry trade, which could lead to virus introduction into non-affected areas ( 29 ). Our study concludes that given the structure of Vietnam’s poultry value chain, which remains highly flexible with numerous middlemen between producer and consumer, closure of LBMs, unless implemented on a longer term and in a larger geographical area or nationwide, will be an ineffective strategy for reducing the risk of AI.…”
Section: Discussion: Value Chain Flexibility and The Ecology Of Aimentioning
confidence: 87%
“…Chilled chickens are slaughtered and packaged chicken stored at between 0°C and 4°C after going through a chilling process and has a shelf-life of 5-7 days, which can highly reduce the risk of virus transmission from live poultry to human [23]. Since the outbreaks of H7N9, many cities that reported the cases have launched a pilot program (named "Centralized Slaughtering, Cold Chain Delivery, Chilled Poultry Supply") in designated areas, such as 2013 in Shanghai, 2014 in Guangzhou and Shenzhen [11]. Furthermore, the long-lasting circulation of the H7N9 virus in market poultry has often preceded the emergence of H7N9 outbreaks.…”
Section: Discussionmentioning
confidence: 99%